2015
DOI: 10.1002/ajmg.a.37388
|View full text |Cite
|
Sign up to set email alerts
|

A familial pericentric inversion of chromosome 11 associated with a microdeletion of 163kb and microduplication of 288kb at 11p13 and 11q22.3 without aniridia or eye anomalies

Abstract: Interstitial deletions of 11p13 involving MPPED2, DCDC5, DCDC1, DNAJC24, IMMP1L, and ELP4 are previously reported to have downstream transcriptional effects on the expression of PAX6, due to a downstream regulatory region (DRR). Currently, no clear genotype-phenotype correlations have been established allowing for conclusive information regarding the exact location of the PAX6 DRR, though its location has been approximated in mouse models to be within the Elp4 gene. Of the clinical reports currently published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Our patient was referred for an ophthalmologic evaluation, which was normal, and her father has normal vision. This post-test clinical evaluation supports the genomic boundaries of the proposed PAX6 regulatory region previously published (Balay et al, 2015), indicating that the deletion is outside of this regulatory region. However, the association of a deletion of this region with the patient’s neurodevelopmental diagnoses and her father’s psychiatric history remains uncertain.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Our patient was referred for an ophthalmologic evaluation, which was normal, and her father has normal vision. This post-test clinical evaluation supports the genomic boundaries of the proposed PAX6 regulatory region previously published (Balay et al, 2015), indicating that the deletion is outside of this regulatory region. However, the association of a deletion of this region with the patient’s neurodevelopmental diagnoses and her father’s psychiatric history remains uncertain.…”
Section: Resultssupporting
confidence: 88%
“…Similar deletions have been identified rarely in both cases and controls (Coe et al, 2014). This deletion is located telomeric to the PAX6 gene and the ELP4 gene, which is thought to harbor a PAX6 regulatory region (Balay et al, 2015). Loss of function or disruption of PAX6 is known to cause aniridia and other ophthalmologic abnormalities (Hingorani et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have found that the 566 kb hemizygous deletion of chromosome 11p13 downstream of PAX6 gene should be the cause of the familial aniridia ( Cheng et al., 2011 ). In addition, the prior studies have also shown that 11p13 interstitial deletion (including DCDC1 gene) can affect the downstream transcription of PAX6 , whereas this effect would result in the occurrences of aniridia and eye deformities ( Balay et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A familial pericentric inversion of chromosome 11 associated with submicroscopic interstitial deletion of 11p13 and duplication of 11q22.3 was presented by Balay et al The 11p13 deletion of 163 kb included the IMMP1L gene and part of the DNAJC24 and ELP4 genes. The patient’s phenotype was characterized by intellectual disability, speech abnormalities, and autistic behaviors; however, nobody in this family presented aniridia or other eye anomalies (Balay et al 2016 ).…”
Section: Pax6 Gene Mutations and 11p13 Microdeletions In Nonmentioning
confidence: 99%